CEFPIROME (CPR) IN THE TREATMENT OF PATIENTS WITH SURGICAL INFECTIONS - OHNO, KOHICHI; MURAMATSU, HIDEYUKI; KINOSHITA, HIROAKI; NAKATANI, SHUICHI; MORIMOTO, KEN; HIRATA, SANAE; FUJIMOTO, MIKIO; UEDA, TAKAMI; SAKAI, KATSUJI; MIZUGAMI, KENJI; OHMORI, KUNIO; MORIMOTO, YUZURU; et al. (CHEMOTHERAPY, 1991)
Between September 1988 and January 1990, we gave cefpirome (CPR) to five subjects after surgery and studied the pharmacokinetics of the drug. In the same period, we treated 20 patients with surgical infections with the same drug and evaluated its clinical effects. 1. In the basic study, 1 g was given intravenously over a 30 min. period. The peak levels in the plasma, 78.4-114 μg/ml, were at around the end of this time. The peak levels in the bile, 10.7-148 μg/ml, were at hours 2-5, depending on the patient. At hours 5 and 6, the range was 10.4-114 μg/ml. 2. In the 20 patients with surgical infection, the clinical efficacy of the drug was excellent in seven, good in nine, fair in one, and poor in two, with an efficacy rate of 84%. 3. The bacteriological response was evaluated in the 16 patients, for whom the species of the probable causative organism could be identified. The bacteria were eradicated in ten patients, decreased in one, were replaced in one, and persisted in four, with an eradication rate of 69%. 4. For the six strains of Pseudomonas aeruginosa isolated, the highest MIC was 6.25 μg/ml, so this drug should be effective toward this species. Two strains of Staphylococcus aureus were isolated, one of which was resistant to methicillin. It was not eradicated.